Isolation and Analysis of Phospholipids in Dairy Foods - Lígia Pimentel; Ana Gomes; Manuela Pintado; Luis Miguel Rodríguez-Alcalá (Journal of Analytical Methods in Chemistry)
The lipid fraction of milk is one of the most complex matrixes in foodstuffs due to the presence of a high number of moieties with different physical and chemical properties. Glycerolipids include glycerol and two fatty acids esterified in positions sn-1 and sn-2 with higher concentration of unsaturated fatty acids than in the triglyceride fraction of milk. Sphingolipids consist of a sphingoid base linked to a fatty acid across an amide bond. Their amphiphilic nature makes them suitable to be added into a variety of foods and recent investigations show that phospholipids, mainly phosphatidylserine and sphingomyelin, can exert antimicrobial, antiviral, and anticancer activities as well as positive effects in Alzheimer’s disease, stress, and memory decline. Polar lipids can be found as natural constituents in the membranes of all living organisms with soybean and eggs as the principal industrial sources, yet they have low contents in phosphatidylserine and sphingomyelin. Animal products are rich sources of these compounds but since there are legal restrictions to avoid transmission of prions, milk and dairy products are gaining interest as alternative sources. This review summarizes the analysis of polar lipids in dairy products including sample preparation (extraction and fractionation/isolation) and analysis by GC or HPLC and the latest research works using ELSD, CAD, and MS detectors.